Penerapan Proses Stokastik Markov Chain Dalam Pengendalian Persediaan Produksi Kelapa Sawit di Perkebunan Nusantara IV Sumatera Utara - Regina Kuswoyo; Sajaratud Dur; Hendra Cipta (G-Tech: Jurnal Teknologi Terapan, 2023)
Problems experienced by PT. Perkebunan Nusantara IV are linked to an inconsistent supply of Fresh Fruit Bunches (FFB). This causes a temporary cessation of production so that CPO production is not in line with the target. The purpose of this study is to predict the rate of increase in raw material production results (CPO) and (FFB) using the Markov Chain Stochastic Process method. From the results of data processing for 2022, the amount of increase in production (CPO) was obtained with an average inventory control value of 1,509,087 Kg. While for the increase in production output (FFB) of 8,200,441 Kg. When compared to production in previous years, it can be seen that there will be an increase in 2021. Based on the results of research from palm oil inventories if the inventory of materials is too small, it will cause losses to the company, it is concluded that the measurement results using the Markov Chain Stochastic Process method show a shift in inventory caused by the age of the inventory, the company must take into account how much inventory is available in order to meet demand period.